The Impact Of Islamic Financal Development And Social Orientation Of Islamic Banks On Income Inequality In Oic Countries - Jamil, Muslimah Mohd (2017)
Three objectives of this study which are to examine the effect of Islamic financial development on income inequality; to investigate the moderating effect of the zakat by Islamic banks in improving the effectiveness of Islamic financial development in reducing income inequality and to analyse whether a more active and higher corporate social responsibility by Islamic banks enhances the effectiveness of Islamic financial development in bringing down income inequality. This study uses 25 OIC countries for the period from 2006 to 2014. The result indicates that Islamic financial development reduces income inequality. Zakat and corporate social responsibility help the Islamic financial development in reducing the income inequality.